2021
DOI: 10.1007/s10856-021-06594-8
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and preliminary quality evaluation of aspirin/L-glutamate compound pellets

Abstract: L-glutamate is an important component of protein. It can prevent gastrointestinal damage caused by NSAIDs. We constructed two-phase enteric-coated granules of aspirin and L-glutamate compound by extrusion spheronization method and fluidized bed coating. The subliminal effective dose of L-glutamate is 100 mg/kg tested by model of gastric ulcer of rats induced by aspirin and drug administration. HPLC-UV and UV–Vis methods were adopted to determine content and cumulative release of aspirin and L-glutamate as qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that glutamate plays an important role in the protection and repair of gastric mucous injuries ( Du et al, 2014 ; Du et al, 2020 ; Xu et al, 2021 ). Glutamate, an important endogenous active substance, is widely present in the central nervous system and peripheral tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that glutamate plays an important role in the protection and repair of gastric mucous injuries ( Du et al, 2014 ; Du et al, 2020 ; Xu et al, 2021 ). Glutamate, an important endogenous active substance, is widely present in the central nervous system and peripheral tissues.…”
Section: Introductionmentioning
confidence: 99%